Bentuk Pelaksanaan Demokrasi Pertama di Indonesia - Teguh Dias Arestu (LP4MK STKIP PGRI Lubuklinggau, 2021)
liberal democracy begins When indenesia has held a session in the KMB to form a parliamentary. As the cabinet progresses, the policy pattern depends on the prime minister who is in charge of his time. Like the burhanudin harahap cabinet which made the first election work program in Indonesia, which threw many countries around